134k views
0 votes
Show that for any positive numbers a and b with a ≠ 1 and b ≠ 1, loga(b) ∙ logb(a) = 1.

User Bojeil
by
5.2k points

1 Answer

3 votes

Answer:

logₓ(y) =
(\log(y))/(\log(x))


(\log(b))/(\log(a))*(\log(a))/(\log(b))

or

= 1

Explanation:

Data provided:

a ≠ 1 and b ≠ 1

To prove
\log_a(b).\log_b(a)=1

RHS = 1

LHS =
\log_a(b).\log_b(a)

Now,

We have the property of the log function as:

logₓ(y) =
(\log(y))/(\log(x))

applying the above property on the LHS side to solve LHS, we get

LHS =
(\log(b))/(\log(a))*(\log(a))/(\log(b))

or

LHS = 1

Since,

LHS = 1 is equal to the RHS = 1

Hence, proved that
\log_a(b).\log_b(a)=1

User Ricardo Tomasi
by
5.7k points